Five-year outcomes of endovascular treatment for aortic dissection from the Global Registry for Endovascular Aortic Treatment - Payne, Davis; Böckler, Dittmar; Weaver, Fred; Milner, Ross; Magee, Gregory A.; Azizzadeh, Ali; Trimarchi, Santi; Gable, Dennis R. (Journal of vascular surgery, 2024)
Objective - The Global Registry for Endovascular Aortic Treatment (GREAT) is an International prospective multicenter registry collecting real-world data on performance of Gore aortic endografts. The purpose was to analyze the long-term outcomes and patient survival rates, as well as device performance in patients undergoing thoracic endovascular aortic repair for acute and chronic and complicated or uncomplicated type B aortic dissection (TBAD). - Methods - From August 2010 to October 2016, 5014 patients were enrolled in the GREAT registry. The study population were patients treated with thoracic endovascular aortic repair for TBAD through 5-year follow-up (days 0-2006). The primary outcomes for this analysis were all-cause and aortic-related mortality, stroke, aortic rupture, endoleaks, migration, fracture, compression, and any reintervention through 5 years. - Results - We identified 265 patients. The mean age was 60.9 ± 11.9 years (range, 19-84 years; 211 males [79.6%]). Devices used were the Gore TAG and Conformable Gore TAG Thoracic Endoprosthesis. There were 228 patients (86.0%) who underwent primary endovascular treatment (144 off-label [54.3%]); 22 (8.3%) underwent reintervention after prior endovascular procedure and 15 (5.7%) underwent reintervention after prior open procedure. Kaplan-Meier estimated freedom from all-cause mortality at 5 years was 71.1%. Freedom from aortic-related mortality through 5 years was 95.8%. There was no significant difference in freedom from all-cause mortality during the follow-up period in complicated or uncomplicated disease. At 30 days and through 5 years, respectively, for all the following outcomes, the aortic rupture rate was 1.1% (n = 3) and 1.9% (n = 5). The stroke rate was 1.1% (n = 3) and 4.2% (n = 11). The spinal cord ischemic event rate was 1.5% (n = 4) and 2.6% (n = 7). Reinterventions were required in 6.4% (n = 17) and 21.1% (n = 56) of patients. The need for conversion to open repair was 0.4% (n = 1) and 2.6% (n = 7). Additional graft placement was required in 3 patients (1.1%) and 16 patients (6.0%). The endoleak rate at 30 days was 3.4% (n = 9); type IA (n = 1 [0.4%]), type IB (n = 4 [1.5%]), type II (n = 1 [0.4%]), type III (n = 1 [0.4%]), and unspecified (n = 4 [1.6%]). Through 5 years, the endoleak rate was 12.1% (n = 32); type IA (n = 7 [2.6%]), type IB (n = 10 [3.8%]), type II (n = 9 [3.4%]), type III (n = 2 [0.8%]), and unspecified (n = 12 [4.5%]). There were no cases of stent migration, compression or fracture through 5 years. - Conclusions - Results at the 5-year follow-up demonstrate that the use of the Gore TAG and Conformable Gore TAG Thoracic Endoprosthesis can be supported in treatment of TBAD (acute, chronic, complicated, and uncomplicated). These data demonstrate strong device durability, beneficial patient outcomes, and support for the treatment of thoracic aortic dissection with an endovascular approach. Complete 10-year follow-up in GREAT as planned will be advantageous.